Teatro do oprimido e educação ambiental : a construção de um guia didático transdisciplinar - Oliveira, Meireane da Costa (2024)
The environmental problems that permeate human existence are countless, and human concerns about these problems have been growing as the situation worsens. In this bleak scenario, it is necessary to rethink the relationship that humanity establishes with the environment. Thus, Critical Environmental Education emerges, supported by critical theory, which presupposes an Environmental Education that questions and problematizes society, fostering the autonomy of thinking and acting in subjects. However, how can we educate environmentally in order to favor the construction of transdisciplinary ecological knowledge, aiming to develop critical and emancipatory attitudes in subjects in the service of social transformation? This work seeks to affirm that the Theater of the Oppressed carried out by Action Research constitutes an important tool for the didactic-pedagogical work of Critical Environmental Education, as both tools, the Theater of the Oppressed and Action Research, enable critical, democratic, reflective and offer emancipatory resources to subjects. Thus, we aim to investigate the potentialities and difficulties of both resources simultaneously, in the development of the necessary skills relevant to the formation of critical subjects capable of fully exercising citizenship. Our investigation was carried out with a voluntary group of 11 students in the final years of Elementary School, from Escola Estadual Souza Bandeira in Cuiabá, Mato Grosso, in the first semester of 2023. During this period we conducted workshops with exercises and theatrical games based on the books Player para actors and non-actors (2015) and The aesthetics of the oppressed (2009), both by Augusto Boal. With the help of pre- and post-test questionnaires, logbooks and conversation circles, we noticed significant changes in the participants' understanding of environmental issues and the concepts covered, such as nature and the environment. Furthermore, we observed the development of the communicative and interpersonal skills of the participating subjects. We understand that Action Research offered space for dialogue and respect between researcher and researched. Facts that attest that the Theater of the Oppressed can be used as a pedagogical tool to work on Critical Environmental Education and promote the exercise of citizenship.